Dampak Implementasi Enterprise Resource Planning di Era 5.0 Terhadap Kualitas Informasi Akuntansi, Nilai Perusahaan, dan Manajemen Laba - Harun Alfahmi; Fauzan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine the impact of Enterprise Resource Planning (ERP) implementation on the quality of accounting information, company value, and earnings management in companies listed on the Indonesia Stock Exchange (IDX) in 2024. Technique used in this study was puposive sampling of 48 company data that met the criteria as observation units, the analysis method used was non-parametric analysis of the Wilcoxon test. The results of this study are that there are significant changes in the quality of accounting information in companies listed on the Indonesia Stock Exchange (IDX) after implementing Enterprise Resource Planning (ERP), there are no significant changes in the value of companies listed on the Indonesia Stock Exchange (IDX) after implementing Enterprise Resource Planning (ERP), and there are no significant changes in earnings management in companies listed on the Indonesia Stock Exchange (IDX) after implementing Enterprise Resource Planning (ERP).